The Role of Allocation in a Globalized Corporate Income Tax - Mintz, Jack (IMF Working Papers; Working Paper ;, 1998)
The internationalization of business activity has created significant pressures on national corporate tax systems. Rather than abandon the corporate tax field, this paper predicts that governments will develop arrangements to further globalize the corporate income tax. The paper assesses the merits and limitations of allocation methods for attributing income to different jurisdictions according to formulas measuring business activity. Such methods are being used as part of transfer pricing regimes and are likely to be enhanced over time. Whatever international arrangements develop in the future, there is a role for new institutions to improve cooperative discussions among governments.